How psychological well-being of adolescent based on demography indicators? - Afdal Afdal; Asmidir Ilyas (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2020)
This study aims to analyze the psychological well-being of adolescents who live with the parents of victims of domestic violence in terms of the demographic aspects of the respondents. Sampling using a purposive sampling technique using certain criteria. The number of samples is 42 people (23 women and 19 men). Each sample has different demographic characteristics. The instrument used was the Psychological Well-Being Scale (PWBS) on the Indonesian Version. Data analysis using Statistical Product and Service Solutions (SPSS) with descriptive techniques. The research results found that: 1) the psychological well-being score of male adolescents was lower than the psychological well-being score of female adolescents; 2) the psychological well-being scores of the Minang ethnic adolescents were higher than the psychological well-being scores of adolescents from other tribes; and 3) the psychological well-being score of adolescents with the educational background of S1 parents is higher than adolescents with other educational backgrounds.